(untitled) (Journal of Intellectual Property and Information Technology Law (JIPIT), 2022)
‘Truth has become elusive.’ ‘We are entering into an age of information apocalypse.’ ‘Seeing is no longer believing unless you saw it live.’ These and similar statements characterise most discussions in the present highly digital age. With the borderless nature of the Internet, it is possible to share videos, photos, and information with countless people provided one has a reliable internet source and a smart gadget, for instance, a mobile phone. Technological advancements have also made it possible for tech-savvy individuals to compile computer programs that make it possible to swap faces and replace them with those of celebrities, politicians, et cetera. Yet even more sophisticated technology uses Artificial Intelligence (AI) methods to create videos and photos that are not easily distinguishable from the real ones. ‘Deepfakes’ has become a buzzword. Along this line, this paper posits that there is widescale misinformation due to deepfakes and assesses the regulation of deepfakes in Kenya to curb the misinformation. It recommends pragmatic ways to train forensic experts and to create awareness among members of the public for detecting deepfakes, hence curbing their negative effects.